Perancangan Sistem Informasi Pariwisata Kabupaten Bulukumba Berbasis Geographic Information System (GIS) - Asnefi, Asnefi (Department of Electrical Engineering, University of Patria Artha, 2020)
Bulukumba Regency is one of the mainstay areas of the tourism sector in South Sulawesi. Some of the tourism objects that are excellent for tourists in Bulukumba Regency are Bira White Sand Beach, Apparalang Beach and Cliffs, Liukang Island, Ammatoa Traditional Area and other tourist objects. Through the design and manufacture of tourism GIS, it is hoped that it can display a picture of the tourist map of Bulukumba Regency so that it is more attractive and can be enjoyed by the wider community. Presentation of information in web form will make it easier for people to access it.The system development methodology used in this study is the Waterfall model Research and Development method. The design of maps displayed in this system uses the Google Maps API, the software used in building this application is PHP (Pear Hypertext Prepocessor) as a programming language, MySQL, XAMPP, and Sublime text.The geographic information system for tourism in Bulukumba Regency is a system that provides information to the public regarding the location of tourist objects in Bulukumba Regency and its supporting facilities. The information presented on this website includes tourist attraction information, descriptions, coordinate points, pictures and travel advice.